Распространение подковоноса малого (Rhinolophus hipposideros Весhstеin) на западе УССР - Татapинов, К.А. (Вестник зоологии, 1972)
Wintering Rhinolophus hipposideros Bechstein are found in the cave above the Svirzh river on the 6-7th of April, 1971 in environs of vii. Melna (Rogation district, Ivano-Frankovsk region). Before that time the above-mentioned species of Chiroptera was known on the right bank of the Dniester only and this river was considered to be the north-western boundary of R. hipposideros Bechstein areal. The finding indicates that at present this species occurs on the left bank of the Dniester, and the north-western boundary of its distribution passes between the towns of Rogation and Lvov.